The role of human emotions in memorable tourism experience and revisit intention - Abhijeet Vikramaditya Tiwari; Naval Bajpai; Prasant Pandey (Tourism & Management Studies)
As tourism research focuses on experience, memorable tourism experience (MTE) is gaining importance among academia and destination managers. However, only limited studies have examined the antecedents and consequences of MTE. Therefore, this study will investigate human emotions with their underlying factors in influencing MTE to cater to revisit intention in tourists. For this study, CFA-SEM is applied to a sample of 1120 tourists from central India to access the empirical relationships. The empirically validated model confirmed the significant relationships among human emotions, MTE, and revisit intention. Results suggested that human emotions significantly influence MTE, which is reflected as revisit intention in tourists. Findings also confirmed the moderating role of the perceived risk of COVID-19 further, exploring the health-linked effects on tourism. This study will help the researchers and destination managers make more informed decisions and strategies to make tourism destinations more sustainable by incorporating human emotions as a significant factor in influencing the tourism experience. The findings will also help destination managers in making tourism more risk-averse.